Level, Uphill, and Downhill Running Economy Values Are Correlated Except on Steep Slopes - Lemire, Marcel; Falbriard, Mathieu; Aminian, Kamiar; Millet, Grégoire P.; Meyer, Frédéric (Frontiers in Physiology, 2021)
The aim of this study was first to determine if level, uphill and downhill running energy cost (ECR) values were correlated at different slopes and for different running speeds; and second to determine the influence of lower limb strength on ECR. Twenty-nine healthy subjects completed a randomized series of 4-min running bouts on an instrumented treadmill to determine their cardiorespiratory and mechanical (i.e., ground reaction forces) responses at different constant speeds (8, 10, 12, and 14 km·h-1) and different slopes (-20, -10, -5, 0, +5, +10, +15 and +20%). The subjects also performed a knee extensor strength assessment. Oxygen and energy costs of running values were correlated between all slopes by pooling all running speeds (all r² ≥ 0.27; p ≤ 0.021), except between steepest uphill vs level and steepest downhill slope (i.e., +20% vs 0% and -20% slopes; both p ≥ 0.214). When pooled across all running speeds, the ECR was inversely correlated with knee extensor isometric maximal torque only in level and downhill running conditions (all r² ≥ 0.24; p ≤ 0.049), except for the steepest slope (i.e., -20%). The optimal downhill grade (i.e., lowest oxygen cost) varied between running speeds and ranged from -14% and -20% (all p < 0.001). The present results suggest that on ~±20% slope, running energetics are determined by different factors (i.e., reduced bouncing mechanism, muscle higher strength in negative slope vs. higher cardiopulmonary fitness level in positive slope) than on shallow slopes. At lower negative slopes and in level running, knee extensor strength is related to ECR.